Підвищення продуктивності інфраструктури для послуг IoT - Сабурова, С. О.; Кухарчук, М. М.; Кадацька, О. І. (ХНУРЕ, 2021)
Presented analysis of improvement of infrastructure for IoT services. While LTE is likely to remain the leading technology for connecting IoT services in the near future, especially given the planned shutdown of 2G and 3G networks in many regions of the world, in the next few years the IoT (Internet of Things) infrastructure expects many implementations of vehicle telematics to support 4G and 5G technologies. Opportunity to evolve 5G networks to deliver improved IoT infrastructure performance and take advantage of the enhanced capabilities of 5G, where 4G and 5G technologies are available while mobile operators continue to evolve their networks.
Keywords: Підвищення продуктивності; Послуги IoT